2014
DOI: 10.1186/s12913-014-0624-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of inhibitors and facilitators for adhering to hypertension treatment among insured patients in rural Nigeria: a qualitative study

Abstract: BackgroundUniversal health care coverage has been identified as a promising strategy for improving hypertension treatment and control rates in sub Saharan Africa (SSA). Yet, even when quality care is accessible, poor adherence can compromise treatment outcomes. To provide information for adherence support interventions, this study explored what low income patients who received hypertension care in the context of a community based health insurance program in Nigeria perceive as inhibitors and facilitators for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 43 publications
5
65
1
Order By: Relevance
“…Studies of similar educational interventions in primary care settings in Europe and the USA recorded lower attendance rates, namely 79% and 58% [23] [41]. The high attendance rate in this study suggests that CHEP responded to patients' needs, which is plausible in the light of a previous qualitative study that was conducted in the area [29]. Secondly, we observed that patients who attended CHEP showed improvements in adherence to medication and behavioral recommendations.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Studies of similar educational interventions in primary care settings in Europe and the USA recorded lower attendance rates, namely 79% and 58% [23] [41]. The high attendance rate in this study suggests that CHEP responded to patients' needs, which is plausible in the light of a previous qualitative study that was conducted in the area [29]. Secondly, we observed that patients who attended CHEP showed improvements in adherence to medication and behavioral recommendations.…”
Section: Discussionsupporting
confidence: 57%
“…The content of CHEP was inspired by a hypertension education program that was developed by Beune et al [23], and results of a previous interview study with hypertensive patients of OOH [29]. All patients were randomly assigned to a group of 12 -15 "trainees" which held the same composition throughout the program.…”
Section: Intervention-chepmentioning
confidence: 99%
See 1 more Smart Citation
“…Odusola et al [40] Qualitative Nigeria Open Journal of Epidemiology selected studies including sampling procedure (random/purposive) population ages, study settings (hospital/clinic/community), study design (cross-sectional/ longitudinal/qualitative) and measurement procedure of medication adherence.…”
Section: Mmas 8 Ghana and Nigeria; N = 357mentioning
confidence: 99%
“…Details of the specific methods employed in the interview studies are reported elsewhere [28,29]. For the literature review a narrative approach was used.…”
Section: Participants and Settingmentioning
confidence: 99%